Corporate engagement with green tax incentives in Malaysia: Awareness to action? - Ariffin, Zaimah Zainol; Sulaiman, Aryati Juliana (International Journal of Accounting, Finance and Business, 2025)
The alarming challenge of climate change has intensified the need for sustainable business practices, particularly within the manufacturing sector. While governments worldwide, including Malaysia, have introduced fiscal instruments such as green tax incentives to encourage environmentally responsible practices, the extent to which these measures are understood and utilized by companies remains unclear. This study addresses this gap by examining the awareness and planning of green tax incentives among manufacturing companies in Malaysia. Data was collected through a structured survey to capture firms’ levels of concern regarding climate change, their awareness of available tax incentive schemes, and their intentions to incorporate sustainability into corporate strategies. The study is significant as it draws attention to the gap between policy availability and corporate readiness to act, a gap that may limit the effectiveness of climate-responsive measures. The findings have important implications for policymakers, emphasizing the need for more effective communication, targeted advisory services, and financial facilitation to ensure that green tax policies achieve their intended environmental and economic outcomes.